THE RELATIONSHIP BETWEEN PARENTS’ SOCIOECONOMIC STATUS AND ORTHODONTIC TREATMENT NEED - Intan Olifia; Widodo Widodo; Renie Kumala Dewi (Dentino: Jurnal Kedokteran Gigi, 2026)
Background: According to Basic Health Research (Riskesdas) data in 2013, the proportion of malocclusion among individuals aged 15-24 years in South Kalimantan was 14.2%. The high proportion of malocclusion may increase orthodontic treatment need. Orthodontic treatment need can be influenced by several factors, including parents socioeconomic status. Purpose: To analyze the relationship between parents socioeconomic status and orthodontic treatment need using the ICON index among high school students in the urban area of Banjarmasin. Methods: This analytic observational study with a cross-sectional design involved 356 high school students aged 15-18 years in the urban area of Banjarmasin who were selected using simple random sampling. Orthodontic treatment need was measured using the Index of Complexity, Outcome, and Need (ICON) through study models, while parents socioeconomic status was assessed using a questionnaire based on Kuppuswamy’s socioeconomic scale. Results: Most parents socioeconomic status was classified as lower-middle (39%). The mean ICON score was 39.77, indicating borderline/moderate orthodontic treatment need. Spearman correlation showed a significant negative relationship between parents socioeconomic status and orthodontic treatment need (p < 0.05; r = -0.464). Conclusion: There is a significant negative relationship between parents socioeconomic status and orthodontic treatment need among high school students in urban Banjarmasin. Students from lower socioeconomic families tended to have higher orthodontic treatment need.Keywords: Adolescents; ICON; Orthodontic treatment need; Parents socioeconomic status